2019
DOI: 10.13189/aeb.2019.070502
|View full text |Cite
|
Sign up to set email alerts
|

Individual Income Tax Revenue and Its Determinants: A Case Study in Vietnam

Abstract: Individual income tax revenue accounts for a high proportion of Vietnam's total tax revenues. The purpose of the article is to study the factors affecting individual income tax revenue in Vietnam. The findings show that there are three factors, which have the strongest impact on the individual income tax revenue including GDP at current prices, individual income tax burden and inflation. Based on the empirical results, the article proposes some policy implications that can increase the individual income tax re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 6 publications
(3 reference statements)
0
2
0
Order By: Relevance
“…К макроэкономическим факторам здесь некоторые авторы добавляют еще поведенческие и другие факторы, в частности расходы на потребление домашних хозяйств, государственные расходы, экспорт и импорт, открытость торговли, прямые иностранные инвестиции, безработицу и коррупцию. Среди них можно выделить работы, посвященные корпоративному налогу на прибыль (Monteiro et al, 2012;Ťahlová, Banociova, 2019), НДС (Bikas, Andruskaite, 2013;Olaoye, 2016;Msangi, 2015;Соколов, 2021), подоходному налогу (Son, Huu Cung, 2019;Alabede et al, 2013), имущественным налогам (Rajul et al, 2020;Bahl, Martinez-Vazquez, 2008) и местным налогам (Hanum, Sari, 2022;Mtasiwa, 2013).…”
Section: обзор релевантных научных источниковunclassified
“…К макроэкономическим факторам здесь некоторые авторы добавляют еще поведенческие и другие факторы, в частности расходы на потребление домашних хозяйств, государственные расходы, экспорт и импорт, открытость торговли, прямые иностранные инвестиции, безработицу и коррупцию. Среди них можно выделить работы, посвященные корпоративному налогу на прибыль (Monteiro et al, 2012;Ťahlová, Banociova, 2019), НДС (Bikas, Andruskaite, 2013;Olaoye, 2016;Msangi, 2015;Соколов, 2021), подоходному налогу (Son, Huu Cung, 2019;Alabede et al, 2013), имущественным налогам (Rajul et al, 2020;Bahl, Martinez-Vazquez, 2008) и местным налогам (Hanum, Sari, 2022;Mtasiwa, 2013).…”
Section: обзор релевантных научных источниковunclassified
“…A secondary time series data set for the years from 2002 to 2011 was used in a study on determinants of individual income tax revenue in Vietnam, the result finds that an increase in GDP per capita is the most important factor effecting individual income tax revenue [2,12]. The empirical study on determinants of individual income tax revenue in Vietnam concluded that there are three factors effecting individual income tax revenue during 2002-2016, such as GDP at current prices, tax burden and inflation [13]. The impact of GDP at current prices and tax burden on individual income tax revenue is a positive significant while inflation has a negative effect on individual income tax revenue.…”
Section: Literature Reviewsmentioning
confidence: 99%
“…For direct taxes, revenue from corporate income tax accounts for the highest proportion in most developing countries, while revenue from individual income tax is the highest in developed countries. Another study calculated that corporate income tax revenue during the period of 2007 -2011, 13.96% in China (ranked the 2nd after VAT), 30.73% in Vietnam (ranked the 1st) [4]. Based on The Huffington Post Canada the first time in Canadian history, more than half of the federal government's revenue in 2014 will come from individual income tax [3].…”
Section: Introductionmentioning
confidence: 99%